Perlecan is required to inhibit thrombosis after deep vascular injury and contributes to endothelial cell-mediated inhibition of intimal hyperplasia - Nugent, Matthew A. (National Academy of Sciences, 2000)
Perlecan, a heparan sulfate proteoglycan, has been suggested to be critical for regulation of vascular repair. We generated clones of endothelial cells expressing an antisense vector targeting domain III of perlecan. Transfected cells produced significantly less perlecan than parent cells and showed a reduced ability to inhibit the binding and mitogenic activity of fibroblast growth factor-2 in vascular smooth muscle cells. Endothelial cells were seeded onto three-dimensional polymeric matrices and implanted adjacent to porcine carotid arteries subjected to deep injury. Although the parent endothelial cells prevented occlusive thrombosis, perlecan-deficient cells were completely ineffective. The ability of endothelial cells to inhibit intimal hyperplasia, however, was abrogated only in part by perlecan suppression. The differential regulation by perlecan of these different aspects of vascular repair may explain why control of clinical clot formation does not lead to full control of intimal hyperplasia. Thus the use of genetically modified tissue-engineered cells provides a new approach for dissecting the role of specific factors within the complex environment of the blood vessel wall.